Hambatan dan Kesenjangan Pelayanan dalam Perawatan Ibu Postpartum: Systematic Literature Review - Yuliani Yuliani (Journal of Literature Review, 2026)
The postpartum period is a critical phase in women's reproductive health because it involves complex physiological, psychological, and social changes and a significant risk of maternal complications. Although postnatal care (PNC) is necessary to ensure maternal recovery and early detection of complications, various studies have shown that barriers and gaps in services persist across various country contexts. These gaps include aspects of access, quality of care, continuity of care, and social and structural factors. This study aims to synthesize empirical evidence regarding the forms of barriers, key determinants, and strategies for reducing discrepancies in postpartum maternal care. This study used a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. The literature search was conducted through the Scopus database using a combination of keywords related to barriers and gaps in postpartum care with Boolean operators. Articles were limited to publications published between 2017 and 2025, in English, and available in full text. Of the 381 identified articles, 20 met the inclusion criteria and were analyzed through narrative synthesis and thematic analysis. Bibliometric analysis using VOSviewer was conducted to map the interrelationships and developments of the research themes. The results indicate that barriers to postpartum care are multilevel, encompassing individual factors (education, health literacy, postpartum depression), socioeconomic and geographic factors, variations in the quality and capacity of service systems, and policy and financing barriers. The most consistent determinants are education level, exposure to antenatal care, socioeconomic status, geographic access, and service quality. Bibliometric analysis indicates a predominance of mental health and clinical management themes, while issues of service equity are relatively underexplored. Postpartum care disparities relate not only to service protection but also to health system quality and continuity. An integrated, multilevel approach is needed to improve the equity and quality of maternal care.